The neglected biliary mucus and its phosphatidylcholine content: a putative player in pathogenesis of primary cholangitis—a narrative review article - Stremmel, Wolfgang (Ann Transl Med, 2021)
Primary sclerosing cholangitis (PSC) is a rare progressive cholangitis resulting in cirrhosis and cholangiocellular carcinoma. The pathogenesis is unclear and an effective medical therapy is not available. It is highly associated to ulcerative colitis for which recently a disturbance of the tight junction (TJ) barrier has been claimed as etiologic feature. Genetic mouse models with intestinal TJ disruption showed a defective transport of phosphatidylcholine (PC) to intestinal mucus. Consequently, an ulcerative colitis phenotype developed. In the present study we evaluate whether there is also a paracellular transport of PC through TJ to the apical side of cholangiocytes. As in ulcerative colitis, a TJ defect could lead to deficient PC in biliary mucus. It would impair the protective barrier against aggressive bile acids in bile. Indeed with polarized biliary tumor cells a vectorial transport of PC from basal to luminal side was demonstrated using a transwell culture system. PC was not taken up by the cells but moved paracellularly via TJ to the apical side driven by luminal HCO(3)− generated by the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) and the anion exchange protein 2 (AE2). If such a TJ-mediated PC translocation to the apical surface of cholangiocytes could be disrupted in a genetic mouse model, a PSC phenotype would be expected. With such an experimental model functional operative therapies can be evaluated. We propose that disruption of TJ mediated paracellular transport of PC to the apical side of cholangiocytes could lead to biliary mucus PC depletion. This may be a pathogenetic factor for development of PSC.